Combinatorial Physical Vapor Deposition : A New Methodology for Exploring Eco‐friendly Composition for Halide‐based Resistive Switching Memory. Issue 18 (25th May 2022) - Lee, SangMyeong; Kim, Won Bin; Kim, Hee Jung; Choi, Jin Hyuk; Lee, Jae Myeong; Gong, Oh Yeong; Jung, Hyun Suk
Abstract: Due to the excellent charge mobility and tunable composition engineering, halide materials are being considered as new resistive switching (RS) memory materials. However, conventional halide materials‐based RS memory devices primarily comprise lead‐based compounds and solution‐based processes, implying that researching new compositions for eco‐friendly RS memory one‐by‐one synthesis would be extremely time consuming. This study reports the fabrication of an eco‐friendly RS memory composition using a combinatorial physical vapor deposition (PVD) technique. The fabricated films are classified into three device types: RS memory, write‐only‐read‐many, and insulator device type, based on the mole fraction of bismuth sulfide (Bi2 S3 ). The 0.75BiI3 –0.25Bi2 S3 mixture devices exhibit reliable and stable RS memory characteristics with an electroforming‐free process. Additionally, the study of cohesive, formation, and migration energies via first‐principles simulations demonstrate that the type of device changes because of their inability to develop and migrate their anion vacancies, implying that the amorphous nature of the device cannot retard the movement of iodine vacancies. This study is the first to investigate a new composition of eco‐friendly halide materials‐based RS memory via the combinatorial PVD method. These findings will serve as a powerful tool for investigating new compositions of eco‐friendly RS memory. Abstract : Adopting combinatorial physical vapor deposition is new paradigm for searching novel compositions for eco‐friendly RS memory. A compositional gradient layer is spatially divided into three device types: RS memory, write‐only‐read‐many, and insulator. Only 0.25 mole fraction of Bi2 S3 device has reliable RS memory characteristics. Moreover, an amorphous nature effect by first‐principles simulations of cohesive, formation, and migration energies is observed.